Time Element In The Construct Of Special Education Teacher Workload In Malaysia - et. al., Irma Shayana Bte Samaden, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Effectiveness in leading can be identified through efficient time management. Quality leaders should make time among the key aspects that need to be addressed. In managing a school that has a special education program, school leaders need to be more sensitive to the needs of students with special needs and the teachers involved. Such a situation needs to be done because full attention should be given by teachers to their students as such students are made up of people with disabilities. Therefore, time management and assignments need to be emphasized because it will affect the productivity of teachers in their teaching to students. This brief study was conducted to detail the relevant elements of time in efficient task management for special education teachers. The findings of this study can be used as a reference for special education teachers and also leadership in special education, so that further issues such as workload, stress and pressure can be avoided.